2005
DOI: 10.1111/j.1753-4887.2005.tb00129.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K and Sphingolipid Metabolism: Evidence to Date

Abstract: The brain is enriched with sphingolipids, which are important membrane constituents and major lipid signaling molecules that have a role in motor and cognitive behavior. Vitamin K has been implicated in brain sphingolipid metabolism for more than 30 years. The in vitro and in vivo studies to date suggest a role of vitamin K in the regulation of multiple enzymes involved in sphingolipid metabolism within the myelin-rich regions in the brain. However, the precise mechanisms of action are not well understood. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 105 publications
(132 reference statements)
1
22
0
6
Order By: Relevance
“…The presence of MK-4 in myelin fractions, and the positive correlations between MK-4 and sulfatides in brain myelin, supports recent findings in female rats [31] suggests the physiological role of MK-4 may be independent from its well-known role as a cofactor for the γ-carboxylation reactions [30, 34, 46]. It is currently not known whether long-term dietary dihydrophylloquinone consumption will modulate these functions through further reduction in dK conversion to MK-4, and whether MK-4 may have a role in myelin formation and maintenance.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The presence of MK-4 in myelin fractions, and the positive correlations between MK-4 and sulfatides in brain myelin, supports recent findings in female rats [31] suggests the physiological role of MK-4 may be independent from its well-known role as a cofactor for the γ-carboxylation reactions [30, 34, 46]. It is currently not known whether long-term dietary dihydrophylloquinone consumption will modulate these functions through further reduction in dK conversion to MK-4, and whether MK-4 may have a role in myelin formation and maintenance.…”
Section: Discussionsupporting
confidence: 83%
“…Vitamin K, a fat-soluble vitamin, has been implicated in regulation of brain sphingolipid metabolism, including sulfatide metabolism [28, 29, 30]. Furthermore, a recent study reported a positive correlation between sulfatides and vitamin K, which is present almost exclusively in the form of menaquinone-4 (MK-4) in the brain [31, 32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Studies with animals support a role for vitamin K in the biosynthesis of sphingolipids which are present in high concentration in the brain. [22][23][24] Although originally known for their role as a structural component of cell membrane, now sphingolipids are known to participate in cell signaling, proliferation, differentiation and survival.…”
Section: Warfarin Teratogenicitymentioning
confidence: 99%
“…2007). The brain has high concentrations of vitamin K (Denisova and Booth 2005), which is essential for the development and many of the functions of the mammalian CNS (Tsaioun 1999; Funakoshi et al. 2002).…”
Section: Fat‐soluble Vitaminsmentioning
confidence: 99%